Mapping Islamic Law Scholarship (2000–2025): Co-citation Structure, Key Authors, and Research Clusters - Judijanto, Loso (West Science Islamic Studies, 2026)
The goal of this research is to analyze the intellectual network structure, prominent publications and thematic trends within the field of Islamic law studies during the period of 2000 – 2025 through the bibliometric methodology. Data was extracted from the Scopus database and was processed using the VOSviewer software to identify co-authorship, citations and keywords. Findings show that a rather homogeneous network structure characterizes this community with some important individuals and institutions making up its core. As for citation analysis, it demonstrates that most of the highly cited works deal with secularism, political Islam, religious/secular dynamics and other topical questions related to the relationship between religion and state. Moreover, the thematic change in research is also evident in keyword analysis. It proves that in addition to traditional themes, which relate to classical Islamic jurisprudence, there appeared several important topics including human rights, gender justice, Islamic feminism, and others.